An application of denoising based on wavelet transform for temperature signals of the alternators in a passenger coach - (:unkn) unknown (My University, 2008)
This paper deals with a passenger coach alternators. In this study, temperature variations, which are depended on load conditions of alternators in a passenger coach, have been investigated using the wavelet transform based denoising and statistical methods. To obtain real road data from the bus alternators, the bus was driven 456 km on the roadway in Turkey. During the collecting alternators data, interior lighting lambs on/off locations, air conditioner operation position, bus headlights situations and other electrical/electronic devices on/off positions have been considered. MATLAB program was used for the signal analysis of the alternators.
Keywords: Alternator; Passenger coach; Temperature signal analysis; Wavelet transformation